2018
DOI: 10.1002/2017jd027734
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of a Simulated Squall Line During Southern China Monsoon Rainfall Experiment to Parameterization of Microphysics

Abstract: A squall line on 22 May 2014 during the Southern China Monsoon Rainfall Experiment period is simulated with four bulk microphysical parameterizations (BMPs) using the Weather Research and Forecasting (WRF) model. Although most BMPs are able to capture the basic features of the squall line, the movement, morphology, and especially the length of the simulated squall lines differ significantly among BMPs. Morrison scheme tends to simulate a slower moving squall line with a weaker cold pool and better trailing str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 75 publications
1
54
1
Order By: Relevance
“…For instance, the changing microphysical cooling rates resulted in different strengths of cold pools (Adams-Selin et al, 2013), where stronger cold pools generally produced stronger RIJs (Weisman, 1992) as well as stronger mesovortices (Atkins and St. Laurent, 2009a). In addition, various microphysical schemes normally led to different convective organizations under the same dynamic regime in previous simulations (e.g., Lawson & Gallus, 2016;Qian et al, 2018). Finley et al (2001) conducted supercell simulations to find that the intensive precipitation due to convective merger led to a rising pressure behind the gust front, and more evaporative cooling caused a stronger cold pool during the bow echo evolution.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, the changing microphysical cooling rates resulted in different strengths of cold pools (Adams-Selin et al, 2013), where stronger cold pools generally produced stronger RIJs (Weisman, 1992) as well as stronger mesovortices (Atkins and St. Laurent, 2009a). In addition, various microphysical schemes normally led to different convective organizations under the same dynamic regime in previous simulations (e.g., Lawson & Gallus, 2016;Qian et al, 2018). Finley et al (2001) conducted supercell simulations to find that the intensive precipitation due to convective merger led to a rising pressure behind the gust front, and more evaporative cooling caused a stronger cold pool during the bow echo evolution.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, microphysical processes could affect the structural evolution of a bow echo significantly (e.g., Atkins and St. Laurent, 2009a; Adams‐Selin et al, 2013; Lawson & Gallus, 2016; Qian et al, 2018). For instance, the changing microphysical cooling rates resulted in different strengths of cold pools (Adams‐Selin et al, 2013), where stronger cold pools generally produced stronger RIJs (Weisman, 1992) as well as stronger mesovortices (Atkins and St. Laurent, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of comprehensive observations and our limited understanding of the microphysical processes of ice‐phase particles, there are many uncertainties not only in the choice of microphysics schemes (Barthlott et al , ; Hazra et al , ) but also in the microphysical parameters used in each scheme (Johnson et al , ; White et al , ). Therefore, parametrizations in microphysical schemes are often tuned so that precipitation intensities and distributions in simulated storms can match observations (Lang et al , ; Qian et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Some conflicting results are obtained when using different microphysics schemes. Luo et al (), Bryan and Morrison (), and Qian et al () noted that a simulation with medium‐density graupel would produce unrealistically larger convective regions, while a high‐density simulation showed a much narrower convective line with higher reflectivity and a smaller stratiform region. Morrison and Milbrandt () and Weverberg et al () found that the faster the hail fall speed, the higher the downward precipitation flux, as a result of the higher melting rate.…”
Section: Introductionmentioning
confidence: 99%
“…Positive impacts of assimilating the observational data from the wind profiler network, operational weather radar, lightning detector are demonstrated on predicting convection evolution over inland South China and northern South China Sea [8]. Rain evaporation represented by microphysics schemes is critical for simulating the formation, movement, and morphology of a linear-shaped MCS passing over the SCMREX field campaign [9]. An experimental convection-permitting ensemble prediction system based on the Global/Regional Assimilation and Prediction System is developed for quantitative precipitation forecast (QPF) over southern China.…”
mentioning
confidence: 99%